ANALYSIS OF QUEUING SYSTEM AT IMMIGRATION OFFICE CLASS II CIREBON - Fatima, Fatima; Pritasari, Adita (Journal of Business and Management, 2017)
Abstrack. In daily activities, people often meet with queuing activity. Queue that often found is payment at mall cashier, buying a movie ticket at CGV, public toilet, Toll exit payment, and queuing at Teller Bank. The queuing line also happens in process making of passport. Passport is an official document issued by an authorized official of a country which contains the identity of the holder and is applicable to travel between countries. The passport is processed at the immigration office. The Immigration Office is a technical implementing unit performing the functions of the Directorate General of Immigration in a certain area or city and an Immigration Office may serve one or more districts and municipalities (General of Immigration, 2014). Immigration office class II Cirebon serves at least 4 districts and municipalities around Cirebon, like Cirebon, Indramayu, Kuningan, and Majalengka. Because of that, there is a long queue line of making a regular passport at the immigration office class II Cirebon. Long queue line can be seen in the taking queue numbers of customer service counters and interview and photo counter of the applicants until served. Waiting room capacity also cannot accommodate the numbers of registered applicants, so that many of them waiting in the parking area and canteen area of immigration office class II Cirebon until served. This research has a purpose of analyzing the queuing system of making regular passport at immigration office class II Cirebon. Queuing system used at immigration office class II Cirebon is model B (M / M / S). The process of data analysis using Microsoft Excel. Data from this research is obtained from the interview and observation. The results of this study indicate that the performance of the queuing system that is used today is not optimal because there are still many customers who queue especially at the interview and photo counters because they must wait for 36 minutes from the maximum standard of waiting 20 minutes. Therefore, the researcher suggests adding one more counter at the interview and photo counters so that the average customer time to wait becomes 14 minutes. Another suggestion is to make the information center counter because in April 2017 the average percentage of applicants who were rejected at the customer service counter by 31%.Keywords: Immigration office class II Cirebon, queuing system, model B (M/M/S).